Quality assurance criteria for assay results in the determination of barium by atomic absorption spectrometry in wastewater by Shewhart control charts - Camero Jiménez, José W. (2013)
This paper defines the criterion of quality assurance results for the determination of barium by the method Standard Methods 3111 D - Direct Nitrous Oxide - Acetylene Flame Method by atomic absorption spectrometry, estimated for individuals Shewhart control limits for accuracy and precision parameters. The study was conducted for wastewater